2017
DOI: 10.1073/pnas.1706985114
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin rotates unidirectionally and generates torque while walking on microtubules

Abstract: Cytoskeletal motors drive many essential cellular processes. For example, kinesin-1 transports cargo in a step-wise manner along microtubules. To resolve rotations during stepping, we used optical tweezers combined with an optical microprotractor and torsion balance using highly birefringent microspheres to directly and simultaneously measure the translocation, rotation, force, and torque generated by individual kinesin-1 motors. While, at low adenosine 5'-triphosphate (ATP) concentrations, motors did not gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
111
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 92 publications
(125 citation statements)
references
References 44 publications
14
111
0
Order By: Relevance
“…The GeNTOP calibration showed that we achieved the optical-trap spring constant-the trap stiffness κ-necessary for kinesin picotensiometry employing microspheres. 6,9,[12][13][14] Also, for the used laser power, the trap stiffness quantitatively agreed with a Mie theory calculation based on the dielectric properties of germanium at the infrared trapping laser wavelength (see methods). Thus, GeNTOPs had indeed the expected very high refractive index of 4.34.…”
Section: Germanium Nanospheres For Ultraprecision Spatiotemporal Meassupporting
confidence: 68%
See 2 more Smart Citations
“…The GeNTOP calibration showed that we achieved the optical-trap spring constant-the trap stiffness κ-necessary for kinesin picotensiometry employing microspheres. 6,9,[12][13][14] Also, for the used laser power, the trap stiffness quantitatively agreed with a Mie theory calculation based on the dielectric properties of germanium at the infrared trapping laser wavelength (see methods). Thus, GeNTOPs had indeed the expected very high refractive index of 4.34.…”
Section: Germanium Nanospheres For Ultraprecision Spatiotemporal Meassupporting
confidence: 68%
“…[1][2][3] However, many such processes cannot be measured at their native spatiotemporal resolution but only under conditionsfor example, low nucleotide concentrations-at which the mechanochemistry is slowed down and might be different. 6 For example, the benchmark, 3.4-Å-DNA-base-pair-sized steps of the RNA polymerase, naturally operating on a millisecond time scale, could only be resolved on a second time scale. 7 The inherent trade-off between temporal and spatial precision and the resolution limit itself are quantified by the product δ √ τ that has a constant value, with the lower limit hardly depending on the experiment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the forward scattered light detects very little of this motion. We suspect that this happens due to the nature of the signals in the forward and backward directions [13,14], the forward scatter being an interference between unscattered light and the scattered light, while the backscattered one being interference between that reflected from the interface and that scattered off the particle. In the case of low amplitude oscillations, the interface oscillates while the particle remains quite unaffected, such that the backscattered detection senses it while the forward scatter does not.…”
Section: Resultsmentioning
confidence: 99%
“…In that conformation, both heads couldn't attach themselves to microtubule lattice at the same time 19 . Considering the fact that the 3kin structure is not accompanied by a bound tail domain that limits free movement 21 and the fact that kinesin is known to rotate round stalk axis 22,23 , we have no reason to doubt its validity. The structure has been analyzed with DomainFinder application 24 .…”
Section: Methodsmentioning
confidence: 99%